PENGARUH PELATIHAN DAN MOTIVASI BERPRESTASI TERHADAP KINERJA PEGAWAI DENGAN KOMPETENSI SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Pegawai Perusahaan Daerah Air Minum Kabupaten Lebak) - Kahfi, Heri Safari; Khurosani, Aan; Suhendra, Indra (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2017)
The purpose of this research is to know the implementation of employees training and achievement motivation on employees performance. Also to determine whether the employees competence mediates employees training and achievement motivation on employees performance in PDAM Lebak. This study uses a quantitative and descriptive approach, using research methods causality. This study was conducted in PDAM Lebak. Samples are 71 respondents and the data were analyzed using WarpPLS. The results of this study show that: 1). employees training is influential positive and significant on employee’s performance, 2). achievement motivation is influential positive and significant on employee’s performance, 3). employees training is influential positive and significant on the competence, 4). achievement motivation is influential positive and significant on the competence, 5). employee’s competence is influential positive and significant on employee performance. Competence partially mediate between employees training and achievement motivation on employee performance.